Nutritional practices of the preschool-aged children and associated factors: A cross-sectional study in Rupandehi district of Nepal - Sharma, Prakash (Journal of Health Promotion, 2022)
Undernutrition is a common problem among Nepali preschool-aged children. Every parent’s feeding practice should be focused on preventing unhealthy eating behaviors of preschool-aged children as it is very difficult to change it in their later life. This study was carried out to assess the key nutritional practices and associated factors among the 3-5-year-old preschool-aged children from their primary caregivers/mothers by employing a quantitative research method. Data were collected through scheduled interviews and observations from mothers/primary caregivers of 394 preschool-aged children who were selected through a multi-stage random sampling procedure in Rupandehi District of Nepal. Binary logistic regression was done to determine the predictors of nutritional practices of preschool-aged children. A p-value less than 0.05 is considered statistical significance. Economic statuses including caste/ethnicity were the main socio-economic and demographic variables to determine the nutritional practices of the preschool-aged children. Findings of the study indicated that majority of preschool-aged children were found in low-level nutritional practices. The preschoolaged children from marginal economic status, including disadvantage-cohorts of the Terai and Dalit, were the victims of the poor nutritional practices. Hence, community-based nutrition education intervention and mothers/caregivers’ awareness programs on feeding practices may be an incredible effort to improve the nutritional status of preschool-aged children if the program is intervened by targeting the background characteristics of the community group.